Acquired Skills of Graduates of a Local Philippine University and its Relevance to Their Present Job: A Tracer Survey - Angelito Bautista Jr; Bradford Antonio Martinez; Isagani Tano; Randel Estacio; Ryan Arago; Gerardo Bautista; Lenard Bien (Universidade Estadual de Alagoas, 2023)
Employers need graduates who are better prepared for the workplace. In the Philippines, higher education institutions (HEIs) must generate competent graduates who can adapt to quickly changing industries, notably skills, and competencies. To assess this, HEIs regularly conduct tracer or employability surveys or studies to ensure that graduates possess the competencies and abilities that employers need and that curriculum is relevant to industry needs. For this reason, the researchers conducted this study to document the employment characteristics, transition to employment, and acquired skills while studying in a local university of graduates from the school year (SY) 2016-2017 to SY 2020-2021. The most prominent finding is that graduates of the local university see that the competencies and skills they acquired while studying in school are beneficial in their careers and help their rankings and salaries. The university's goal of being the number one choice for employable graduates is manifested in the workplace.